Synthesis and Anticancer Activity of Bis(2-picolyl)amine Derivatives with a Biaryl Moiety as a Photosensitizer - Yoshimi Ichimaru; Koichi Kato; Koushirou Sogawa; Daichi Egawa; Hideaki Kato; Kazuaki Katakawa; Wanchun Jin; Masaaki Kurihara; Hiromasa Kurosaki (Chemistry)
Metal complexes have potential applications in drug discovery due to their unique properties. For example, zinc(II) ions (ZnII) exhibit a high affinity for DNA and have been used as active centers in artificial protein/small-molecule metallonucleases. In this study, we designed a series of ligands containing a biaryl moiety as a photosensitizer to synthesize ZnII complexes with enhanced DNA affinity for use as DNA photocleavage reagents. The DNA photocleavage activity of these complexes was evaluated using the pUC19 plasmid, revealing that the ZnII complex bearing the 4′-biphenyl-bpa (bpa = bis(2-picolyl)amine) ligand L1 exhibited the strongest DNA photocleavage activity. Further analysis of the biological activity of the ZnII complex of L1 in the human pancreatic cancer cell line MIA PaCa-II demonstrated that its cytotoxic activity increased in a UV irradiation time-dependent manner, with an IC50 value of 14.2 μM. Fluorescence staining revealed that the ZnII complex of L1 generates reactive oxygen species in cells, leading to DNA double-strand breaks upon UV irradiation and ultimately resulting in necrotic cell death. These findings highlight the potential of the ZnII complex of L1 as a photochemotherapeutic agent for pancreatic cancer.